(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This article proposes reflections on the teaching and dissemination of Animation Theater through cyberspace, investigating how social isolation could stimulate a certain awareness of the everyday look, recognizing in it elements that lead us to animated forms. Based on reports about the experience in a virtual workshop, offered during the coronavirus pandemic, we discuss here what it means to know this universe composed of puppets, objects, shadows and mask.